Exploring Mental Health Awareness among Bachelor of Science in Office Administration Students : A Case Study at the University of Saint Anthony, Philippines - Belmonte, Sheena M.; Ciron, Jennifer H.; Nacario, Reynalyn C. (Journal of Public Health Sciences, 2023)
This study aims to determine the mental health awareness of Bachelor of Science in Office Administration students at the University of Saint Anthony. Specifically, it seeks to identify the respondents' profile in terms of age, gender, and year level, as well as the factors affecting their mental health, challenges they face that may lead to mental health problems and ways to manage such issues. Moreover, based on the study findings, the study aims to develop a mental health awareness guide to help students cope with their situations. The researcher used the descriptive research method, which involves a survey questionnaire to gather data. The study's findings indicate that most respondents sleep for 4-6 hours per day, feel anxious most of the time, and experience emotional problems that affect their studies. Many respondents sometimes experience fear, anxiety, or panic attacks, feel lonely or alone, and have mood swings, particularly anxiety. However, most respondents' mental health status is average, and they do not plan to attempt suicide over the last 12 months. Based on the study's conclusions, the recommendations include ensuring students sleep enough to avoid negative feelings such as irritability and stress. It is also suggested that students take care of themselves and have enough rest, especially at night, to think clearly and feel good when they wake up. Seeking help or guidance from trusted individuals such as teachers, counsellors, or classmates is also recommended.